Estudo retrospectivo de dez anos de cirurgia bariátrica sobre os fatores de risco cardiometabólicos, atividade física e qualidade de vida - Costa, Larissa Monteiro (2018)
Introduction: Obesity brings about an individual's health, such as type 2 diabetes, systemic arterial hypertension, dyslipidemia associated with an increased risk for cardiovascular diseases. Physical activity tends to improve comorbidities associated with obesity, assists in weight control and has a positive impact on individuals' quality of life. However, psychosocial variations may affect the disposition of individuals in the practice of physical activity after bariatric surgery (BS). Objective: To evaluate the evolution of individuals' level of activity, quality of life after CB, clinical parameters, laboratory parameters and cardiometabolic risk factors at 12 months after BS in groups of different years attended by the single health system in the last 10 years. Methods: 78 patients undergoing bariatric surgery (BS) participated in the study. The subjects were divided into four groups: 12 individuals aged 1-2 years of CB (BS 2), 14 individuals aged 2-4 years CB (BS 4), 22 individuals 4-6 years CB (BS 6), and 30 individuals between 6-10 years of CB (CB + 6). Weight, BMI, percentage of overweight, biochemical indicators, comorbidities associated with obesity (ACRO), physical activity level through IPAQ and quality of life evaluated by BAROS were evaluated. The ANOVA (One Way), Bonferroni Post Hoc test for BAROS and PEP in the different groups was used to verify the possible differences between groups divided by postoperative time of CB. For the other indicators analyzed, ANOVA (Two Way), (Group X Moments) and Bonferroni Post Hoc tests were used. In relation to ACRO, individuals were counted in relation to the cutoff point. Results: There were improvements in body weight at different times, in BMI, in waist circumference, with significant changes in the lipid profile in the first 12 postoperative months, improvement in cardiometabolic risk, systemic arterial hypertension, dyslipidemia and diabetes mellitus after BS. The level of physical activity increased significantly in BS2, BS4, BS6, in the first year of postoperative and had a fall in the current moment maintaining the classification of assets, IPAQ 1 year BS2 (207.50 ± 30.79 min), BS4 (210.67 ± 33.69 min), BS6 (220.00 ± 42.78 min). In BS2 and BS4 quality of life as excellent, BS4 and BS + 6 as very good. Conclusion: Bariatric surgery predisposes the practice of physical activity tends to have a positive result on the comorbidities and the improvement of the quality of life. The level of physical activity after bariatric surgery increased in the different groups investigated while the number of subjects with diabetes, dyslipidemia and hypertension, decreased in all groups over time, with significant differences in the lipid profile of the different groups.